Classical business cycles in Latin America: Turning points, asymmetries and international synchronisation - Mejía Reyes, Pablo (Estudios Económicos de El Colegio de México, 1999)
A classical business cycles approach is applied to study turning points, asymmetries and international synchronisation of business cycle regimes (expansion/recession) for several Latin American countries. The results suggest that recessions are characterised by deeper change, less persistence, and greater volatility than expansions. However, existing evidence about intra-regional economic transactions suggests that these associations might be explained by similar economic policies and common external shocks.